Monitoring CO Pollutants in Ambient Air Quality in Public Spaces of Padang City - Fernandez, Donny; Frinaldi, Aldri; Umar, Genius; Rembrandt, Rembrandt; Lanin, Dasman; Juanda, Ahmad (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
Air pollution in urban areas is a multidimensional threat with systemic impacts on the environment and public health. Carbon monoxide (CO), as a toxic gaseous pollutant from the incomplete combustion of fossil fuels, is the focus of this study which evaluates the spatial-temporal distribution of CO concentrations in public spaces of Padang City during 2020-2024. Using a Systematic Literature Review (SLR) approach and longitudinal environmental data from four strategic points, a significant decrease in CO levels was found from 14,596 µg/m³ (2020) to 286 µg/m³ (2024). Peak concentrations occurred in the dry season, reinforcing the influence of meteorological variables. These results emphasize the importance of real-time digital monitoring systems, multi-sectoral emission policy reformulation, and integration of green open spaces in urban planning. In the future, monitoring should be expanded to other pollutants, congestion locations, and linked to public health early warning systems to support urban sustainability and resilience.